Costs of diarrhoea and acute respiratory infection attributable to not handwashing: the cases of India and China. Issue 1 (January 2017) - Townsend, Joy; Greenland, Katie; Curtis, Val
Abstract: Objective: To estimate the national costs relating to diarrhoea and acute respiratory infections from not handwashing with soap after contact with excreta and the costs and benefits of handwashing behaviour change programmes in India and China. Methods: Data on the reduction in risk of diarrhoea and acute respiratory infection attributable to handwashing with soap were used, together with World Health Organization (WHO) estimates of disability‐adjusted life years (DALYs) due to diarrhoea and acute respiratory infection, to estimate DALYs due to not handwashing in India and China. Costs and benefits of behaviour change handwashing programmes and the potential returns to investment are estimated valuing DALYs at per capita GDP for each country. Results: Annual net costs to India from not handwashing are estimated at US 23 billion (16–35) and to China at US 12 billion (7–23). Expected net returns to national behaviour change handwashing programmes would be US 5.6 billion (3.4–8.6) for India at US 23 (16–35) per DALY avoided, which represents a 92‐fold return to investment, and US 2.64 billion (2.08–5.57) for China at US 22 (14–31) per DALY avoided – a 35‐fold return on investment. Conclusion: Our results suggest large economic gains relating to decreases in diarrhoea and acute respiratory infection for both India and China from behaviour change programmes to increase handwashing with soap in households.